The Future of ATMs in the Era of Electronic Banking in Cameroon: A Survival Analysis - Huboh, Samuel Ringmu; Takoutio, Virginie Feudjio; Njong, Mom Aloysius (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2024)
The future of automated teller machines (ATMs) has come under scrutiny due to the swift expansion of electronic banking in Cameroon. The lifespan of ATMs in Cameroon is being examined in this study using survival analysis methodologies, given the growing popularity of electronic banking. We estimate the ATM survival function and find factors impacting ATM survival using a dataset of ATM installations and deletions from 2004 to 2022. According to our findings, the median lifespan of ATMs in Cameroon is roughly eight years. The acceptance rate of electronic banking, the use of mobile banking, and the degree of urbanisation are important factors that influence the longevity of ATMs. 40% of Cameroon's present ATMs are expected to be retired by 2027. Our findings indicate the necessity for Cameroonian banks and financial institutions to modify their business plans and make investments in electronic banking infrastructure.